The Garrison at Morne. St. Lucia W.I - M. & C. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2020)
This is a picture of the Garrison at Morne. St. Lucia. W. I. “In the latter part of the 19th century, Morne Fortuné served as a garrison to defend the Castries Harbour, which was then a coaling station.” Taken from website: https://slunatrust.org/sites/morne-fortune/ 17053 is imprinted in the image M. & C. 33 Info. Handwritten at the back of postcard: £10
Landscape, Black & white, 4 x 6 in.
Keywords: Military facilities; Barracks; Buildings; St. Lucia- Morne -Garrison